3D printing and enteric coating of a hollow capsular device with controlled drug release characteristics prepared using extruded Eudragit® filaments. (21st October 2021) - Choudhury, Dinesh; Murty, Upadhyayula Suryanarayana; Banerjee, Subham
Abstract: This work focuses on the extrusion of a brittle, tacky, cationic copolymer i.e. Eudragit® E-100 to prepare filament and subsequent 3D printing of hollow capsular device using the extruded filament. An optimum amount of talc and triethyl citrate was used for the possible extrusion of the polymer. There was no thermal and chemical degradation of the polymer observed after extrusion confirmed by DSC and FTIR analysis. Microscopic analysis of the printed capsule showed the layer-by-layer manner of 3D printing. Capsule parts were printed according to the set dimensions (00 size) with minimal deviation. Printed capsule showed the soluble behaviour in gastric fluid pH 1.2 where within 15 min the encapsulated drug encounters with the dissolution medium and almost 70% drug was dissolved within 4 hr. In case of phosphate buffer pH 6.8, the printed capsule showed a longed swelling behaviour up to 12 hr and then gradually bursting of capsule occurred wherein more than 90% encapsulated drug was dissolved within 36 hr. Enteric coating of the printed capsule showed similar behaviour in alkaline medium that observed with non-enteric capsule. This indicates the potential application of this printed capsules for both gastric and intestinal specific delayed drug delivery by a single step enteric coating process. Graphical Abstract: UF0001